Make tracks : Building Site - Dyrander, Johnny (Nosy Crow Inc., 2023)
"Discover four different building site vehicles in this new series of interactive board books with easy-to-use moving parts. Learn vehicle vocabulary with simple first words, clear diagrams and helpful text prompts to encourage discussion. Then trace 4 types of transport around 4 different tracks with a moving counter on every spread and the cover. The perfect book for children who love diggers and dump trucks - and being in the driving seat!"--
Cover title.
On board pages with moving pieces to drive around the tracks.
Keywords: Toy and movable books; Board books